THE ROLE OF SECURITY AWARENESS AND EMPLOYEE BEHAVIOR IN CREATING A SAFE WORK ENVIRONMENT CULTURE - Elbir, Umut (International Scientific Journal Vision, 2024)
It examines the role of security awareness and employee behavior in creating a safe workplace culture. Occupational health and safety consists of the measures and practices taken to ensure the safety of employees in workplaces. However, more than technical measures are needed; Employees’ security awareness and behavior are also critical in maintaining a safe work environment. Safety awareness refers to the ability of employees to recognize risks in the workplace, take precautions against these risks, and exhibit correct behavior in the face of dangerous situations. Employees with high safety awareness actively prevent occupational accidents and strengthen the overall occupational safety culture. The article discusses the impact of training programs, security communication, and leadership behaviors in improving security awareness. Regular safety training provided to employees increases their awareness of occupational safety and helps reflect this awareness in daily business life. Additionally, managers’ and leaders’ attitudes toward safety directly affect employees’ behavior. A safety-focused leadership approach contributes to making safe behavior the norm in the workplace. Safety awareness and safe behaviors form the cornerstones of occupational safety culture. Strengthening these two factors enables the reduction of occupational accidents and the sustainability of a safer work environment.